Gastric metastasis subsequent to renal cell carcinoma surgery: a case report - Junqiao Yao; Xiangyu Meng; Yanmei Zhu; Dong Yang; Jun Zhang; Chao Wang; Yuanlin Liu; Tao Zhang (Frontiers in Oncology)
Gastric metastasis of renal cancer involves the dissemination of renal cancer cells to the stomach via hematogenous or lymphatic routes, leading to the formation of metastatic tumors. Renal cell carcinoma (RCC), a highly aggressive malignant tumor, exhibits a significant propensity for metastasis. Common metastatic sites include the lung, bone, liver, and brain. This report presents a case of gastric metastasis originating from renal cell carcinoma in a 62-year-old male patient who was diagnosed with clear cell renal cell carcinoma in the left kidney in March 2024. The gastric space-occupying lesion was confirmed through imaging studies, gastroscopy, and histopathological examination. This case is documented herein to enhance clinical awareness and improve diagnostic accuracy for this rare manifestation of RCC.